The Co-occurrence of Self-Harm and Aggression: A Cognitive-Emotional Model of Dual-Harm - Shafti, Matina; Taylor, Peter James; Forrester, Andrew; Pratt, Daniel (Frontiers in Psychology, 2021)
There is growing evidence that some individuals engage in both self-harm and aggression during the course of their lifetime. The co-occurrence of self-harm and aggression is termed dual-harm. Individuals who engage in dual-harm may represent a high-risk group with unique characteristics and pattern of harmful behaviours. Nevertheless, there is an absence of clinical guidelines for the treatment and prevention of dual-harm and no agreed theoretical framework that accounts for why people may engage in this behaviour. The present work aimed to address this gap in the literature by providing a narrative review of previous research of self-harm, aggression and dual-harm, and through doing so, presenting an evidence-based theory of dual-harm - the cognitive-emotional model of dual-harm. This model draws from previous studies and theories, including the General Aggression Model, diathesis-stress models and emotional dysregulation theories. The cognitive-emotional model highlights the potential distal, proximal and feedback processes of dual-harm, the role of personality style and the possible emotional regulation and interpersonal functions of this behaviour. In line with our theory, various clinical and research implications for dual-harm are suggested, including hypotheses to be tested by future studies.